(3GdYhGed GdLOjOI aj GdfMhs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi eMeO hBdg CLeYjfhHYO aGYde Cfg dGHO dcd WGdH eYQaI GdEYQGH ef eYQaI eGFI TjA SJhf efgG jSei YGedG hKdGKhf eYehdG hYTQI jSei YedG hEYQGHGs
(3BNQgG (B:s
(3hEf de jXgQ hHd bOQ aj BNQg jSei JbOjQG hde jbOQ aj BNQg jSei eMdjG fMh JhcdfG Ydi ef dG jCJj GdNjQ EdG ef LgJg fMh CfG GdbGVj hEf de jXgQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 61s
(3eYLe GdeDdajf(B: 3 / 176s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs